Used Learning at Al-Irsyad Bulaan Kamba Islamic Boarding School - Levan's, Olivia; Tanucan, Jem Cloyd M.; Garzozi-Pincay, Rene Faruk (Yayasan Pendidikan Islam Daarut Thufulah, 2022)
In today's modern era, technological developments are very influential in education. The activity of using digital applications in media learning for al-Irsyad Islamic boarding school students is carried out with the aim of increasing student interest in learning because with the mixpad application students can channel their talents in sound editing. The mixpad application is expected to be a means of introduction and learning about the use of the mixpad application. Given the current era, not everyone also understands the use of technology. This study aims to determine the effectiveness of using the mixpad application as a medium for learning Arabic in al-Irsyad Islamic boarding school. The research method used is descriptive qualitative research. In the world of education, the media used is the mixpad application. This media is software that serves to hone students' skills in speaking foreign languages, especially Arabic. How to use this application by installing on a laptop or computer, after we are allowed to use this media, input the recording or it can be recorded directly on the recorder, and finally to remix different recording inputs so that the resulting sound looks interesting. The results of this study indicate that students can increase their interest in learning Arabic through audio that is heard by the teacher.